THE INFLUENCE OF COLLATERALIZED ASSETS, PROFITABILITY, INCOME TAX, NON-DEBT TAX SHIELD, FIRM SIZE AND GROWTH ON CAPITAL STRUCTURE - EMIR KHARISMAR; STELLA SUMANTRI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The objective of this research is to get empirical evidence about the influence of collateralized assets, profitability, income tax, non-debt tax shield, firm size and growth on capital structure. The sample of this research is 43 observations from real estate and property companies listed in Indonesia Stock Exchange. The choosing of the samples is based on purposive sampling technique which is continuously registered in Indonesia Stock Exchange during the period of 2006 until 2010. The result of this research showed that collateralized assets, income tax and non-debt tax shield have influence to capital structure. While profitability, firm size and growth have no influence to capital structure.